Cable shared dual-frequency catheter for intravascular ultrasound - Su, Min (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2019)
This study proposes a catheter consisting of dual-frequency transducer for intravascular ultrasound. Both ultrasonic elements with different frequencies were connected to one coaxial cable to make the connection simple. The aperture size of the ultrasound elements were 0.4×0.6 mm2 and 0.3×0.4 mm2 for the low frequency element and high frequency element, respectively. The center frequency and bandwidth of the fabricated low frequency transducer were 33.8 MHz and 49.3%, respectively. Meanwhile, the center frequency and bandwidth of the high frequency transducer were 80.6 MHz and 50.3%, respectively. Imaging evaluations of wire phantom, tissue phantom and vessel tissue demonstrated good imaging capability of the dual-frequency catheter. The spatial resolution are 19 μm axially and 128 μm laterally for the high frequency transducer, and 37 μm axially and 199 μm laterally for the low frequency transducer. Band-pass filters were designed to separate the mixed echo signals. After filtering, the images from different ultrasound elements can be successfully identified, indicating the feasibility of the proposed cable shared dual-frequency imaging strategy. The proposed method has simple structure, good imaging resolution, and large penetration depth, showing good application prospect for intravascular ultrasound